2018
DOI: 10.2147/cmar.s172395
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter arterial chemoembolization monotherapy vs combined transcatheter arterial chemoembolization–percutaneous microwave coagulation therapy for massive hepatocellular carcinoma (≥10 cm)

Abstract: BackgroundThe prognosis of massive hepatocellular carcinomas (MHCCs; ≥10 cm) remains worse.PurposeThe aim of this study was to evaluate the clinical benefits of transcatheter arterial chemoembolization (TACE) or TACE combined with percutaneous microwave coagulation therapy (PMCT) and the long-term survival rate of MHCC patients treated with these techniques.Patients and methodsA retrospective study was performed using data involving 102 MHCC patients admitted to the Second Hospital of Nanjing from September 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Identification flow of the studies is exhibited as Figure 1 and Data . A total of 36 eligible studies 39–74 involving a large sample amount of 5036 patients were included finally for the systematic review and meta‐analysis (Figure 1, Table 1, Data ). All of the included studies 39–74 were published in SCI journals and included in the Web of Science with good quality of reports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Identification flow of the studies is exhibited as Figure 1 and Data . A total of 36 eligible studies 39–74 involving a large sample amount of 5036 patients were included finally for the systematic review and meta‐analysis (Figure 1, Table 1, Data ). All of the included studies 39–74 were published in SCI journals and included in the Web of Science with good quality of reports.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 36 eligible studies 39–74 involving a large sample amount of 5036 patients were included finally for the systematic review and meta‐analysis (Figure 1, Table 1, Data ). All of the included studies 39–74 were published in SCI journals and included in the Web of Science with good quality of reports. The main features of the included trials 39–74 are detailedly presented in Table 1 and Data .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study demonstrated that TACE following percutaneous microwave coagulation therapy in HHCC patients was an ideal treatment strategy. The 6-, 12-, and 18-month OS rates for HHCC patients were 50%, 41.67%, and 16.67% in the combination therapy group [ 22 ]. In our study, the HHCC patients with subsequent combination therapy revealed a longer OS in the high-TGR group, which was in accordance with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…TACE is recognized as an efficient and safe therapeutic procedure for unresectable multifocal and massive hepatocellular carcinoma (HCC). [ 4 , 5 ] By inducing ischemia and necrosis of tumor tissue through arterial chemoembolization, TACE efficiently suppresses the development of liver cancer and can be applied to recurrence, which occurs quite commonly in HCC; therefore, TACE contributes to tumor control and retreatment. [ 6 , 7 ] Given its feasibility and safety, TACE has been utilized for liver cancer for decades; nevertheless, postembolization syndrome (PES), which refers to a series of typical symptoms including fever, abdominal pain, and nausea/vomiting generally induced by TACE, turns out to be a notable clinical issue related to prognosis.…”
Section: Introductionmentioning
confidence: 99%